(untitled) (Revista Brasileira Multidisciplinar, 2021)
Agricultural activity has great national relevance, mainly due to extensive management, based on the use of forages, for which they still need to be better studied from the nutritional point of view, mainly about the use of organic substrates. The objective of this research was to analyze the effect of organic substrates on development Brachiaria brizantha cv. Marandu, in greenhouse conditions. The experiment was conducted at School Farm of University of Araraquara (UNIARA), with the treatments related to standard soil (100%) (T1), in addition to other treatments with different concentrations of organic substrates: Standart soil (80%) + Genesolo® (20%) (T2); Standart soil (80%) + Tanned cattle manure (20%) (T3); Standard soil (80%) + Tanned chicken manure (20%) (T4); and Standard soil (80%) + Organic soil (10%) (T5). For each treatment were conducted five replicates, each corresponding to a 15L polyethylene vessel. Seedling transplantation was performed between 15-20 days after emergence and, as parameters of analysis, three cuts were made, at 10-cm in height from the soil surface, conducted every 60 days after seedling transplantation, aiming to collect material to evaluate the average weight of fresh and dry matter of the aerial part of plants. The organic substrates significantly improved the development of B. brizantha cv. Marandu, with emphasis on the use of tanned chicken manure and tanned cattle manure, especially when related up to 120 days after seedling transplantation.